Economic and environmental feasibility of re‐routing the Indo‐Sri Lankan shipping channel: A green initiative of sustainable development. (16th November 2021) - Kandasamy, Jayakrishna; Nadeem, Simon Peter; Kumar, Anil; K.E.K, Vimal; Nikhil, Hrishikesh Bedekar; Solanki, Nikhilkumar Himatlal
Abstract: As the maritime industry forms the common means of heavy freight transportation, the efficient and strategic management of sea routes from an economic and environmental perspective has become a major concern to achieve sustainable development goals (SDGs). By applying marine engineering principles and quantifying metrics such as energy efficiency design, index/existing vessel design index, energy efficiency operational index, carbon footprints, fuel consumption, voyage times and emission this study aims to explore the merits of the Indo‐Sri Lankan shipping canal project over the existing route circumnavigating Sri Lanka. The quantification was performed by studying the design and operational indices of marine vessels, based on the metrics considering the major ports in India. The socio‐political, environmental and economic benefits reported in this study advocate the significance of this route to the maritime industry in meeting SDGs.